Analysis of mathematical critical thinking skills on the Pythagorean theorem based on self-confidence and gender - Puspa Sari Dewi; I Ketut Suastika; Nur Farida (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze and describe students' mathematical critical thinking skills in terms of self-confidence and gender. This research employed a qualitative descriptive approach. The study was conducted in class VIII-H of SMPN 17 Malang, involving a total of 31 students. From this class, 12 students were selected as research subjects based on gender to participate in a written test. The data collection techniques included questionnaires, written tests, interviews, and field notes. Data analysis was conducted based on the results of the self-confidence questionnaire, written test results, and interviews, which referred to critical thinking indicators. To ensure data validity, techniques such as prolonged engagement, triangulation, peer discussion, and member checking were employed. Based on the results and discussion, it can be concluded that: (1) the research subjects were better able to fulfill the evaluation indicators, (2) female students demonstrated higher self-confidence than male students, (3) higher levels of self-confidence, both in the high and low categories, were associated with higher written test results, and (4) female students tended to meet more critical thinking indicators.